The Portrayal of Indonesian Political Actor’s and Media’s Perspective on the Issue of Climate Change in the 2007 United Nations Climate Change Conference - Yoseph Bambang Wiratmojo; Davidson Willy Arguna Samosir (Jurnal Ilmu Komunikasi, 2012)
The decisions made at the 2007 United Nations Climate Change Conference, in Nusa Dua Bali, have the potential to influence environmental policies in countries around the world, particularly policies to reduce global carbon emissions. This paper analyzed how the Indonesian media portrayed climate change issues during the Conference and the whether the Indonesian media and political actors have the same perspective on climate change issues. After examining approximately 160 news articles and press releases from political actors it was clear that the media and political actors, particularly environmental NGOs, paid careful attention to climate change. However, we found that the Indonesian government did not seriously manage this issue in the media, despite having the responsibility and authority to make environmentally friendly policies. Abstrak2007 United Nations Climate Change Conference diNusa Dua Bali merupakan even yang sangat penting, bukan hanya bagi Indonesia sebagai tuan rumah konferensi, tetapi juga bagi umat manusia di dunia, karena keputusan tentang pengurangan emisi karbon global akan dapat memengaruhi kebijakan tentang lingkungan hidup diseluruh negara dibumi ini. Penelitian ini menjawab pertanyaan tentang bagaimana media diIndonesia menyajikan isu masalah perubahan iklim kepada audiensnya danmencari tahu bagaimana aktor-aktor penentu kebijakan lingkungan mempunyai pemahaman tentang masalah perubahan iklim. Metode analisis dilakukan dengan analisis framing dengan menganalisis 160 artikel media dan pressrelease dari harian KOMPAS, REPUBLIKA, Kementrian Lingkungan Hidup Indonesia, WALHI, dan GREENPEACE Indonesia selama-sepanjang-setelah even 2007 UNCCC diselenggarakan danhasilnya menemukan bahwa media dan NGO menganggap sangat serius issue perubahan iklim ini, namun pemerintah Indonesia tidak menganggapnya serius, sehingga pemerintah Indonesia tidak serius dalam mengorganisasikan issue masalah perubahan iklim ini, padahal mereka adalah penentu kebijakan utama pengurangan emisi karbon.